Pengembangan Modul Ajar Pencemaran Lingkungan dengan Materi Realitas Lokal Indralaya pada Jenjang SMA Kelas X - Nike Anggraini; Shofi Rohmawati; Meilinda Meilinda; Masagus Muhammad Tibrani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research is a type of development research which aims to develop the Merdeka Curriculum teaching module with material on environmental pollution accompanied by material on the local reality context of Indralaya which is suitable to be donated or used at the class X high school level. This research includes development research (development research) which uses a model ADDIE development consists of 5 stages, namely analysis, design, development, implementation and evaluation, where the evaluation carried out is a formative evaluation. The assessment results from the validators obtained a feasibility score of 85.16% with several suggestions given as well as the conclusion from the two validators that the product being developed could be tested with improvements according to the suggestions. After the development stage, an evaluation stage is carried out, namely by improving it according to suggestions from the validator. The results of trials with students showed that all students who were respondents could understand and read the contents of the teaching module being developed. According to the results obtained, the Merdeka Curriculum teaching module product on environmental pollution along with material on the local reality context of Indralaya has been successfully developed and received a feasibility validation score in the very valid category.